Laminar flow continuous settling crystalliser. Part 1. Initial exploration. (September 2017) - Shaffer, Konrad R.; Paterson, Anthony H.J.; Davies, Clive E.; Hebbink, Gerald
Abstract: Conventional lactose crystallisations give large spans that are not suitable for direct use in inhaler grade lactose. The factors causing large spans are successive nucleation events and growth rate dispersion. This paper (Part 1 of 2) explores a novel lactose crystallisation technique, laminar flow continuous settling crystallisation, proposed as a method for directly producing a narrow particle size distribution with a span of less than 1. A theoretical model was developed that modelled the growth and settling of individual crystals with growth rate dispersion within a column full of lactose solution flowing upwards in laminar flow. The model predicted a d 50 of 73.2 ± 0.9 μm and a span of 0.47 ± 0.01. In an experimental crystalliser crystals obtained had a d 50 between 50 and 90 μm but the span was greater than 1. The difference has been attributed to agglomeration and flow variations from true laminar flow, which is reported in Part 2.